Analysis of adhesive joints used to bond FRP laminates to steel members – A numerical and experimental study - Haghani, Reza (Construction & building materials, 2010)
The strengthening of existing structures using bonded fiber reinforced polymer laminates has attracted a great deal of attention in recent years. However, when compared with concrete structures, the application of this method for strengthening structural steel members is somewhat limited. This is mainly due to the lack of an established design code for treating FRP-strengthened members. Issues such as the complexity of failure modes and the lack of knowledge of the force-transfer mechanism are obstacles that contribute to the difficulty associated with developing accurate design models. A few studies have underlined the need for new design approaches to strengthening steel members, since the existing design methods are not accurate enough. The first step towards developing new design models is to study these adhesive joints. This paper deals with analyses of adhesive joints used to bond CFRP laminates to steel substrates using a numerical and experimental approach. A numerical study of joints has been made utilizing the FE method, while, in the experimental part of the study, an optic measurement technique has been used. Different aspects of joint behavior, such as strain distributions along the bond line and through the thickness of the adhesive layer and failure mechanisms are discussed.